84.3k views
2 votes
Rewrite cos(x+4pi/3) in terms of sin(x) and cos(x)

2 Answers

5 votes

Answer:

x8659-3358468854---6666x

User Valath
by
4.6k points
2 votes

Answer:


(√(3) )/(2) sinx -
(1)/(2) cosx

Explanation:

using the sum identity for cosine

cos(a + b) = cosacosb - sinasinb

then

cos(x +
(4\pi )/(3) )

= cosxcos(
(4\pi )/(3)) - sinxsin(
(4\pi )/(3) )

[
(4\pi )/(3) is an angle in the third quadrant where sin and cosine < 0 ]

[ the related acute angle to
(4\pi )/(3) =
(4\pi )/(3) - π =
(\pi )/(3) ]

= cosx × - cos(
(\pi )/(3) ) - sinx × - sin(
(\pi )/(3) )

= cosx × -
(1)/(2) - sinx × -
(√(3) )/(2)

= -
(1)/(2) cosx +
(√(3) )/(2) sinx

=
(√(3) )/(2) sinx -
(1)/(2) cosx

User Supun Kavinda
by
4.6k points